2005
DOI: 10.1586/14737175.5.3.315
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal buprenorphine in the treatment of chronic pain

Abstract: The transdermal matrix patch formulation of buprenorphine has been shown to be effective in managing moderate-to-severe cancer pain and severe pain unresponsive to nonopioid analgesics. Clinical trials have revealed that it is possible to switch from weak opioids or low doses of step III opioids to transdermal buprenorphine without any problems. With buprenorphine patches, the sublingual buprenorphine intake was dose-dependently reduced and was superior to placebo in this respect. The proportion of responders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This association might reflect that patients with chronic pain feel that they need increased doses of buprenorphine to relieve their comorbid pain. This hypothesis is consistent with current off-label prescribing practices for chronic pain patients reported in the pain management literature, in the form of sublingual threeor four-times-a-day dosing (Heit & Gourlay, 2008) and as a transdermal formulation in Europe (Sittl, 2005). However, there are four other primary alternative possibilities: (a) Pain patients with opioid dependence, compared with heroin users without chronic pain, might have developed stronger connections with sources of illicit prescribed opioid medication (e.g., dealers who sell or family and friends who share); (b) people with chronic pain are at an increased risk of illicit use; (c) opioid-dependent patients with pain are more likely to test buprenorphine before officially seeking OBOT treatment; and finally, (d) reducing pain might merely be a marker for an inability to tolerate distress.…”
Section: Self-treatment Of Painsupporting
confidence: 87%
“…This association might reflect that patients with chronic pain feel that they need increased doses of buprenorphine to relieve their comorbid pain. This hypothesis is consistent with current off-label prescribing practices for chronic pain patients reported in the pain management literature, in the form of sublingual threeor four-times-a-day dosing (Heit & Gourlay, 2008) and as a transdermal formulation in Europe (Sittl, 2005). However, there are four other primary alternative possibilities: (a) Pain patients with opioid dependence, compared with heroin users without chronic pain, might have developed stronger connections with sources of illicit prescribed opioid medication (e.g., dealers who sell or family and friends who share); (b) people with chronic pain are at an increased risk of illicit use; (c) opioid-dependent patients with pain are more likely to test buprenorphine before officially seeking OBOT treatment; and finally, (d) reducing pain might merely be a marker for an inability to tolerate distress.…”
Section: Self-treatment Of Painsupporting
confidence: 87%
“…In post-marketing surveillance studies and in a multicenter randomized controlled clinical trial, the transdermal patches were reported to be effective and well-tolerated in the treatment of cancer and non-cancer chronic pain (Griessinger et al, 2005; Sittl, 2005; Sorge and Stittl, 2004; Sittl, Nuijten, & Nautru, 2006). A transdermal formulation of buprenorphine is not presently available in the United States.…”
Section: A Possible Role On the Use Of Buprenorphine For The Treatmenmentioning
confidence: 99%
“…However, these dosing regimens had many disadvantages such as inconvenient management of chronic pain caused by the need for frequent administrations per day, and the possibility of the manifestation of drug toxicity due to sudden peaks in plasma drug concentrations. Therefore, transdermal delivery systems (TDS) have recently been introduced to overcome such disadvantages by maintaining a constant blood drug concentration at an effective level for analgesia and eliminating the frequent dosing (25)(26)(27)(28)(29)(30)(31) required for the management of chronic pain.…”
Section: Introductionmentioning
confidence: 99%